Effects of Conduction Variation on MHD Natural Convection Flow Along a vertical Flat Plate - Islam, AKM Safiqul; Alim, MA; Karim, Md Rezaul; Rahman, ATM M (GANIT: Journal of Bangladesh Mathematical Society, 2016)
This paper reports free convection flow along a vertical flat plate with conduction variation on magneto hydrodynamic (MHD) effects. The governing equations with associated boundary conditions reduce to local non-similarity boundary layer equations for this phenomenon are converted to dimensionless forms using a suitable transformation. The transformed non-linear equations are then solved using the implicit finite difference method together with Keller-box technique. Numerical results of the velocity and temperature profiles, skin friction and surface temperature profiles for different values of the magnetic parameter, the Prandtl number and the conduction variation parameters are presented graphically. Detailed discussion is given for the effect of the aforementioned parameters. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 63-73